Intranasal Lidocaine for Primary Headache Management in Emergency Department; a Clinical Trial - Barzegari, Hassan; Motamed, Hassan; Ziapour, Behrad; Hajimohammadi, Majid; Kadkhodazadeh, Mina (Archives of Academic Emergency Medicine, 2017)
Introduction: Most of the headache cases only require pain management in emergency department (ED). The present study aimed to evaluate the efficacy of intranasal lidocaine in this regard. Method: In this clinical trial, adult patients with primary headache were randomly treated with 7.5 mg intravenous (IV) chlorpromazine and 1 ml intranasal lidocaine 2% (treatment) or normal saline 0.9% (placebo), and were compared 5, 15, and 30 minutes later regarding success rate using SPSS 21. Result: 100 patients were assigned to either treatment or placebo group. Number needed to treat of intranasal lidocaine at 5, 15, and 30 minutes were 4 (95% CI: 2.2 – 6.6), 3 (95% CI: 1.7 – 3.5), and 4 (95% CI: 2.3 – 15.9), respectively. These measures for absolute risk reduction were 30 (95% CI: 15.2 – 44.8), 44 (95% CI: 28.7 – 59.3), and 26 percent (95% CI: 6.3 – 44.3), respectively. Pain relapse occurred in 16% of treatment and 11% of control group within 1 hour of treatment (p = 0.402). Conclusion: It seems that, intranasal lidocaine along with IV chlorpromazine could result in more successful and faster management of primary headaches in ED.